Impact of Employee’s Behavior and Culture on Organizations Productivity in Pharmaceutical Industries of Bangaluru - Murahari Naik*, Arun Babu Angadi, D. (Recent Research in Science and Technology, 2011)
The study was conducted to test the hypothesis using stratified and simple random sampling survey with a questionnaire. Social and cultural traits of individuals haveÃ‚Â to play strong role on the performance of job in industries. The present study reveals the impact of employeeÃ¢â‚¬â„¢s behavior and culture on job performance as well as organizational productivity in Bangalore pharmaceutical industry. On the basis of this scores of hypothesis were made: I. There is no positive relationship between employee behaviour and culture on the productivity. So it will not give any impact on the financial health of the organization. II. There is no positive relationship between employeeÃ¢â‚¬â„¢s behaviour and culture on employee performance.Ã‚Â 90% of the employees strongly agree that there is a relationship between employee behaviour and culture on employee productivity and continuous performance in the organization. Survey findings made me to accept alternative hypotheses and reject null hypothesis. In both the cases calculated values of chi-square are higher than the tabulated values. The study helps to ascertain employeeÃ¢â‚¬â„¢s behavior and cultural effect on the productivity of the organization and helps to formulate recommendations to improve.